Bergamot Polyphenolic Fraction supplementation improves metabolic balance, endothelial function and maximal oxygen uptake in athletes - Mollace, R.; Gliozzi, M.; Tavernese, A.; Musolino, V.; Carresi, C.; Scicchitano, M.; Palma, E.; Nucera, S.; Bosco, F.; Scarano, F.; Oppedisano, F.; Maretta, A.; et al. (Journal of Sports Medicine and Therapy, 2018)
Background: The study aimed to evaluate the effects of a 4-week Bergamot Polyphenolic Fraction (BPF Gold; Bergamet Sport) supplementation on serum nitric oxide (NO), asymmetric dimethyl-arginine (ADMA), Endopat indices of endothelial function and maximal oxygen uptake (V_ O2max) of athletes.